Independent Urine Measurement Based on Internet of Things - Agustiyowati, Tri Hapsari Retno; KD, Sansri Diah; Taryudi, . (KnE Life Sciences, 2021)
This study aims to create an independent urine measuring instrument based on the internet of things (IoT). This study was to see the differences in uroflometric measurements using an independent urine measuring based IoT tool compared to uroflometry in the urology clinic. The sampling method used was consecutive sampling with a total of 32 respondents. Uroflometry measurements were carried out twice, first using an independent urine measuring device based on the IoT, secondly using the standard uroflometric peak flow rate examination in the urology clinic. The results of measuring the average amount of urine per second using an independent urine measuring device based on IoT 22.22 ml / second, the average peak flow rate using uroflometry in the urology clinic is 23.97 ml / second, this shows that an independent urine measuring instrument based on IoT is not significantly different from uroflometry in urology polyclinic with a p value of 0.411, which indicates Ho was accepted, meaning there was no difference between the mean amount of urine per second and the average peak flow rate using uroflometry in the urology clinic. This study therefore concludes that an independent urine measuring devise based on the IoT instrument is effective for measuring urine emission per second. Suggestion: Follow up on the patent and legality of measuring instruments Keywords: independent urine measuring instrument, internet of things(IoT), uroflometry, urethral stricture